Comparative Genomic Analysis of 130 Bacteriophages Infecting Bacteria in the Genus Pseudomonas - Ha, Anh D.; Denver, Dee R. (Frontiers in Microbiology, 2018)
Bacteria of the genus Pseudomonas are genetically diverse and ubiquitous in the environment. Like other bacteria, those of the genus Pseudomonas are susceptible to bacteriophages which can significantly affect their host in many ways, ranging from cell lysis to major changes in morphology and virulence. Insights into phage genomes, evolution, and functional relationships with their hosts have the potential to contribute to a broader understanding of Pseudomonas biology, and the development of novel phage therapy strategies. Here we provide a broad-based comparative and evolutionary analysis of 130 complete Pseudomonas phage genome sequences available in online databases. We discovered extensive variation in genome size (ranging from 3 to 316 kb), G+C percentage (ranging from 37- 66%), and overall gene content (ranging from 81-96% of genome space). Based on overall nucleotide similarity and the numbers of shared gene products, 100 out of 130 genome sequences were grouped into 12 different clusters; 30 were characterized as singletons, which do not have close relationships with other phage genomes. For 5/12 clusters, constituent phage members originated from two or more different Pseudomonas host species, suggesting that phage in these clusters can traverse bacterial species boundaries. An analysis of CRISPR spacers in Pseudomonas bacterial genome sequences supported this finding. Substantial diversity was revealed in analyses of phage gene families; out of 4,462 total families, the largest had only 39 members and there were 2,992 families with only one member. An evolutionary analysis of 72 phage gene families, based on patterns of nucleotide diversity at nonsynonymous and synonymous sites, revealed strong and consistent signals for purifying selection. Our study revealed highly diverse and dynamic Pseudomonas phage genomes, and evidence for a dominant role of purifying selection in shaping the evolution of genes encoded in them.